2015
DOI: 10.1038/srep12607
|View full text |Cite
|
Sign up to set email alerts
|

Steric Interference of Adhesion Supports In-Vitro Chondrogenesis of Mesenchymal Stem Cells on Hydrogels for Cartilage Repair

Abstract: Recent studies suggest the presence of cell adhesion motifs found in structural proteins can inhibit chondrogenesis. In this context, the current study aims to determine if a polyethylene glycol (PEG)-modified fibrinogen matrix could support better chondrogenesis of human bone marrow mesenchymal stem cells (BM-MSC) based on steric interference of adhesion, when compared to a natural fibrin matrix. Hydrogels used as substrates for two-dimensional (2D) BM-MSC cultures under chondrogenic conditions were made from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The results indicated that cartilage ECM was deposited in the hydrogel, adjacent cartilage tissue growth was facilitated by MSCs, and significantly more cartilage tissue formation was found compared to the control group with microfracture treatment. Another composite hydrogel based on PEGDA-fibrinogen (commercially known as GelrinC™ for cartilage repair) has been shown to support enhanced chondrogenesis of MSCs with minimizing hypertrophy [184], which suggested that composite hydrogels can be designed for improved ability to regenerate cartilage tissues.…”
Section: Designing Hydrogels For Reconstruction Of Osteochondral Imentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that cartilage ECM was deposited in the hydrogel, adjacent cartilage tissue growth was facilitated by MSCs, and significantly more cartilage tissue formation was found compared to the control group with microfracture treatment. Another composite hydrogel based on PEGDA-fibrinogen (commercially known as GelrinC™ for cartilage repair) has been shown to support enhanced chondrogenesis of MSCs with minimizing hypertrophy [184], which suggested that composite hydrogels can be designed for improved ability to regenerate cartilage tissues.…”
Section: Designing Hydrogels For Reconstruction Of Osteochondral Imentioning
confidence: 99%
“…Commercially available hydrogel biomaterials for CTE [312] include collagen, fibroin, and HA. PEG [183, 313] and PEG-fibroin [184, 314] hydrogels have progressed to clinical testing. There are still some barriers to the clinical translation of the more complex hydrogel based constructs.…”
Section: Challenges Of Cell-laden Hydrogel Strategies For Oce and Otementioning
confidence: 99%
“…UV irradiation is also normally used on engineered cartilage. A number of studies have shown the substrate’s physical properties and its topological structures to be critical for the chondrocyte’s differentiation, redifferentiation, and maturation [246]. A suitable substrate for seeding cells may help cartilage regeneration through mechanical, biological, and chemical effects in cartilage regeneration [247].…”
Section: Physical Stimulation For Cartilage Regenerationmentioning
confidence: 99%
“…In a three‐dimensional poly(ethylene glycol) (PEG) hydrogel, the carboxylic group chemically tethered on PEG network was found to support the best chondrogenic differentiation of human MSCs among a series of small chemical groups . Most recently, the design of surface chemistry to prevent cell adhesion and induce cell aggregation has been reported to promote chondrogenesis of MSCs . For instance, by employing two polyelectrolytes with opposite charges, poly( l ‐glutamic acid) and chitosan, a hydrophilic surface in three‐dimensional scaffolds was developed and aggregation of rabbit adipose‐derived MSCs was encouraged, showing improved chondrogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%